Environmental degradation assessment of biodiesel production using life cycle analysis - Che Hassan, Che Hafizan (2016)
The global transportation sector is one of the major fuel consumers and contributes directly to greenhouse gas emissions. In order to reduce the environmental burden of fuel usage, new diesel blending formulations that consist of biofuels were developed. The objective of the study is to assess the environmental performance of the new diesel blending formulations compared to the existing diesel blending formulation (B5). The life cycle assessment (LCA) methodology has been used to assess the environmental performance of the blending formulation. New weighting values are also developed by using an analytical hierarchy process to support the study within Malaysia’s context. In term of LCA result within midpoint categories, Blending 5 has shown the most potential compared to other fuels including B5 blending due to better environmental performance in most categories except for ozone depletion and urban land occupation impacts. In the endpoint categories, for Malaysia’s context; Blending 5 has shown better environmental performance as compared to B5 blending with each scoring 9.63E-5 point and 1.00E- 4 point, respectively. The result is found to be consistent with other weighting methods. In developing new weighting values, this study suggests there is no consensus in term of importance between regional and global impact categories. This is visualized in the individualist perspective where both global and regional impacts were scored most importance but higher regional impact scored in egalitarian and hierarchist perspectives. In conclusion, Blending 5 has scored the least weighting values as compared to other diesel blending formulations including B5 thus indicating its potential as an alternative to the existing diesel blending formulation.